Inggit Garnasih, Soekarno and the Age of Motion in Indonesia - Suwirta, Andi (ASPENSI in Bandung, Indonesia, 2009)
ABSTRACT: It seemed relevant to discuss the role and figure of strong, tough and faithful woman in accompanying his husbandâs struggle to realize his social aspiration. Such a woman figure was Inggit Garnasih, Soekarnoâs wife since the period of national movement in Indonesia (1923-1943). In this context, it seemed relevant talking about the services of Inggit Garnasih not based on herself but according to otherâs acknowledgement closely related with her. The other whom I meant was Soekarno, as her husband, as had been stated in his autobiography and other reviewer of Soeakrnoâs biography, especially when it was related to his relationship with Inggit Garnasih. However, Inggit Garnasih did not only encourage her husband to complete his study in THS Bandung but she was also faithful to accompany her husband â in happiness and sorrow â in national movement struggle. Finally, one of statements for reflecting here is that the Republic of Indonesiaâs government should give fair honor to Inggit Garnasih for her services in the age of motion in Indonesia with Soekarnoâs idependence struggle.Â KEY WORDS: Inggit Garnasihâs roles, Soekarnoâs struggle, the age of motion, and Indonesiaâs independent.About the Author: Andi Suwirta, M.Hum. is a Lecturer at the Department of History Education, Faculty of Social Studies Education UPI (Indonesia University of Education) in Bandung; and Editor-in-Chief of EDUCARE: International Journal for Educational Studies in Bandung, West Java, Indonesia. He can be reached at: andisuwirta@yahoo.com or atriwusidna@gmail.comHow to cite this article? Suwirta, Andi. (2009). âInggit Garnasih, Soekarno and the Age of Motion in Indonesiaâ in TAWARIKH: International Journal for Historical Studies, Vol.1(1) October, pp.71-82. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia], ISSN 2085-0980. Chronicle of the article: Accepted (August 19, 2009); Revised (September 19, 2009); and Published (October 28, 2009).